Clinical application of Sri Lankan traditional formulae (Sétärämavaöé and Denibädi Kashäya) in the management of Ürdhvajatrugata Roga: a survey based study - Karunarathna, H.M.H.L.; Peiris, R.M.; Samaratunga, U.; Dharmapriya, A.K.H. (Department of Shalya Shalakya,Gampaha Wickramarachchi Ayurveda Institute,University of Kelaniya,Sri Lanka, 2017)
The history of Sri Lankan traditional medicine dates back to the period of riñi Pulasthi and king Rävaëa. It consists of a vast range of indigenous drug formulae in the management of various kinds of diseases. There are a number of authentic texts related to traditional medicine. Vaöikä Prakaraëaya is one such authentic classic which was written in the 18th century. The formulae used for this study was obtained from Vaöikä Prakaraëaya. The objective of the study was to identify clinical application of Sétäräma Vaöé and Denibädi Kañäya in the management of Ürdhvajatrugata Roga. One hundred indigenous medical practitioners were randomly selected for this study. The data were collected through a specially designed questionnaire. In the literature review of the formulae, Bin kohomba (Munronia pinnata) and Kudumirissa (Toddalia asiatica) were identied as native plants in Sri Lanka.Another specic feature is that Lunuwarana (Crateva adansonii) which is mostly used in the urinary tract diseases in Ayurveda, has been used to treat diseases in the Ürdhvajatrugata Roga in traditional medicine. The results revealed that 100% of physicians use this combination for Çiro Roga, especially in Kaphaja and Vätaja Çiro Roga. Apart from that, many physicians (85%) use it for PénasRoga. 45% of physicians use it for Karëa Roga, especially in Karëa Päka and Karëa Sräva and 40% of physicians use it for Näsä Roga, especially in Kaphaja Pratiçyä. Further, Akñi Roga (30%) and Mukha Roga (20%) were also treated by the physicians using this formula. Therefore, it can be concluded that most of the indigenous physicians in Sri Lanka use this traditional formula in the management of a wide range of Ürdhvajatrugata Roga.
Keywords: sitarama vati; denibadi kasaya; Ürdhvajatrugata Roga